Electroreflectance imaging of gold-H3PO4 supercapacitors. Part II: microsupercapacitor ageing characterization. Issue 4 (28th January 2016) - Saviers, Kimberly R.; Kundu, Arpan; Maize, Kerry; Shakouri, Ali; Fisher, Timothy S.
Abstract : The electroreflectance technique is shown to be an effective method for visualizing ageing behavior of microsupercapacitors. Abstract : This microsupercapacitor ageing study demonstrates the usefulness of the electroreflectance technique by quantifying local charge accumulation. Two separate devices with interdigitated electrodes were evaulated over a period of 4.1 million charge/discharge cycles. The key results are spatial mapping of charge accumulation in the gold electrodes derived from variation in the observed electrode reflectance. The nominal device exhibited little change in spatial distribution throughout the ageing cycle and serves as a comparison for the test device, which exhibited some nonuniform charge accumulation behavior. Further, an accelerated ageing test was completed by applying increasing voltage pulses up to 1.46 V to the device. Visual evidence of electrode ageing emerged in the reflectance distribution. An equivalent circuit model was developed to assess the evolution of individual circuit elements that correlate to the physical causes of ageing.